The effect of a dual‐wavelength 532 nm and 1064 nm picosecond‐domain laser with a fractionated holographic optic on photoaging and patient age perception: A pilot study. (15th December 2021) - Leight‐Dunn, Hayley; Hadi, Ali; Patel, Forum; Yao, Christopher J.; Tu, Yingqi Michelle; Chapas, Anne
Abstract: Introduction: This study evaluated the efficacy of a dual‐wavelength 532 nm/1064 nm Nd:YAG picosecond‐domain laser with a holographic lens array in treating facial photoaging. Methods: Thirteen subjects were enrolled with 10 completing the study. Receiving three‐month treatments, subjects underwent full‐face spot treatment of facial lentigines with the 532‐nm non‐fractionated handpiece, followed by two sequential facial passes of the 1064‐nm and the 532‐nm fractionated handpieces. Improvement was measured by treating physician evaluation of pigmentation and rhytids as well as blinded reviewer evaluation of pre‐ and post‐treatment image sets taken 12 weeks after the final treatment. Participants completed treatment surveys to assess satisfaction. Results: Physician grading on a 5‐point scale revealed an average improvement of 1.6 in pigmentation ( p = 0.0042) and 0.9 in rhytids ( p = 0.0196). Blinded physicians appropriately selected baseline images in 44 of 50 (88%) image sets (10 subjects; five reviewers). On an 11‐point scale for overall facial photoaging (0 = no change, 1 = 10% improvement, 2 = 20% improvement, etc.) treating physicians scored mean improvement as 3.3 ± 1.83 (95% CI 1.99 to 4.61; range 1–6), while blinded reviewers scored mean improvement as 2.32 ± 2.62 (range % −4 to 8, 95% CI 1.57 to 3.07). The greatest majority (80%) of participants reported satisfaction with the treatment. Adverse events were mild; however, one patient developed hyperpigmentation, consistent with melasma that was successfully treated with topical agents. Conclusion: This is the first study to show that picosecond‐domain 532 nm/1064 nm laser treatments with combination non‐fractionated and fractionated handpieces are well‐tolerated, safe, and effective for the treatment of photodamage.